Adaptive Speed Control System Based on Interval Type-2 Fuzzy Logic - Al Mashhadany, Yousif Ismail (Transactions on Engineering and Computing Sciences, 2014)
This paper presents the design and simulation of adaptive control system based on an Interval Type-2 Fuzzy Logic Controller (IT2FLC) with multilevel inverter (MLI) for control of power system, and the command line programming for constructing, editing, and simulating the IT2FLC. The modification was done by considering new membership functions (MFs) for the environment of an Interval Type-2 Fuzzy Logic System (ITFLS). Two other controllers besides the designed IT2FLC, comparing their outputs: a PID Controller and a Type-1 Fuzzy Logic Controller (T1FLC). Various design phases for the fuzzy system, from initial description to final implementation. In this work, the case study is consider for brushless DC (BLDC) motor that is driven by multilevel inverter based on discrete three-phase pulse width modulation (DPWM) generator that forced-commuted the IGBT’s three-level converters using three bridges to vectored outputs 12- pulses with three levels. Using DPWM with a three-level inverter solves the